1980
DOI: 10.1002/jobm.3630201005
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of a silicate and carbonate copper ore with heterotrophic fungi and bacteria, producing organic acids

Abstract: Leaching of metals with carbon-heterotrophic microorganisms and organic acids as active agents has been performed with Timna copper ore containing 1.1% copper as carbonates and silicate and with some other metal oxides. Aspergillus niger surface cultures on a 14% sucrose fermentation medium yeilded 87.3% of total copper from 10% suspension within 2 weeks of leaching. On sulfite liquor as an industrial waste product A. niger solubilized 73.8% Cu within 4 weeks. In percolators with 14% sucrose medium up to 1780 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Some heterotrophic microorganisms are also characterized by a high metal tolerance. Wenberg et al (1971) and Kiel and Schwartz (1980) reported on copper leaching experiments that were carried out successfully with fungi (yields of 80%). Heterotrophic bacteria were successfully applied in the leaching of manganese and gold (Ehrlich, 1980;Pares, 1968).…”
Section: Copper and Antimony Extraction From Tetrahedrite-containing mentioning
confidence: 95%
See 1 more Smart Citation
“…Some heterotrophic microorganisms are also characterized by a high metal tolerance. Wenberg et al (1971) and Kiel and Schwartz (1980) reported on copper leaching experiments that were carried out successfully with fungi (yields of 80%). Heterotrophic bacteria were successfully applied in the leaching of manganese and gold (Ehrlich, 1980;Pares, 1968).…”
Section: Copper and Antimony Extraction From Tetrahedrite-containing mentioning
confidence: 95%
“…For the reasons mentioned above, the application of heterotrophic microorganisms in leaching silicate/carbonate materials has certain advantages. Weathering experiments have shown that fungi and heterotrophic bacteria grown on silicate and carbonate ores were able to attack and destroy the ores by producing organic acids (Wagner and Schwartz, 1967;Kiel and Schwartz, 1980). Metal leaching in these instances was based on a completely different principle than with T. ferrooxidans.…”
Section: Copper and Antimony Extraction From Tetrahedrite-containing mentioning
confidence: 97%
“…Biocatalytic activity of A. niger has been reported to be helpful in leaching of metals from ores [40]. Organic acids (oxalic acid, citric acid, gluconic acid, etc.)…”
Section: Effect Of Sucrose Concentrationmentioning
confidence: 99%
“…Both autotrophic (Torma and Bosecker, 1982) and heterotrophic (Kiel and Schwartz, 1980;Sukla and Panchanadikar, 1983;Munier-Lamy and Berthelein, 1987) microorganisms possess the potential to remove nickel from its ores.…”
Section: Introductionmentioning
confidence: 99%